Construction of Double-Shelled Hollow Ag2S@Polydopamine Nanocomposites for Fluorescence-Guided, Dual Stimuli-Responsive Drug Delivery and Photothermal Therapy - Minjie Gao; Zehua Han; Xu Zhang; Xueyan Zou; Lichao Peng; Yanbao Zhao; Lei Sun (Nanomaterials, 2022)
The design and preparation of multifunctional drug carriers for combined photothermal–chemotherapy of cancer have attracted extensive attention over the past few decades. However, the development of simple-structured stimuli-responsive theranostic agents as both photothermal agents and chemotherapeutic agents remains a big challenge. Herein, a novel double-shelled nanocarrier composed of hollow Ag2S (HAg2S) nanospheres and a mesoporous polydopamine (MPDA) exterior shell was fabricated through a facile process. Notably, HAg2S possesses both fluorescence and photothermal properties. MPDA acts as a drug carrier and photothermal agent. Meanwhile, the cavity structure between HAg2S and MPDA provides more space for drug loading. The nanocarrier presents a high drug loading rate of 23.4%. It exhibits an apparent pH-responsive DOX release property due to the acidic sensitivity of PDA. In addition, the release of DOX is promoted under NIR irradiation, which is attributed to the heating action generated by the photothermal effect of HAg2S and MPDA. The cytotoxicity test shows that the nanocarriers possess good biocompatibility. Compared with single photothermal therapy or chemotherapy, the combined treatment represents a synergistic effect with higher therapeutic efficacy. In addition, the nanocarriers exhibit excellent fluorescence imaging capability and can target HepG2 cells. These simple-structured smart nanocarriers have a great potential for fluorescence-mediated combination cancer therapy.